(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The feeding effects of DoLa (a combination of Dayak onion extract and probiotic Lactobacillus acidophilus) on hematological indices and lymphoid organs as indicators of broiler health status were evaluated in the present study. Materials and Methods: 192 1-day-old unsexed broilers of the CP 707 strain with a body weight of 46.43 ± 1.65 gm were randomly divided into 4 dietary treatments with 6 replications. The dietary treatments applied were basal diet (BD) as a control with a code of DoLa0, BD + 0.1% DoLa (DoLa1), BD + 0.2% DoLa (DoLa2), and BD + 0.3% DoLa (DoLa3). The parameters monitored included hemoglobin (Hb), red blood cell (RBC), heterophile (H), lymphocyte (L), white blood cell (WBC), heterophile-lymphocyte (H/L) ratio, the lymphoid organs (bursa Fabricius,spleen, and thymus) relative weight, as well as carcass weight. Results: The results indicated a significant improvement in WBC, L, and carcass weight (p < 0.05) as the feeding level of DoLa increased while the H and H/L ratio decreased. However, the dietary inclusion of DoLa did not affect the lymphoid organs’ relative weight, RBC, and Hb concentrations. Conclusion: The mixture at 0.3% significantly improved health status through the indicators of hematological indices, lymphoid organs, and carcass weight of broilers. J. Adv. Vet. Anim. Res., 10(2): 269–274, June 2023 http://doi.org/10.5455/javar.2023.j678